Seasonal Control of Gonadotropin-Inhibitory Hormone (GnIH) in Birds and Mammals - Kriegsfeld, Lance J. (Front Neuroendocrinol, 2014)
Animals inhabiting temperate and boreal latitudes experience marked seasonal changes in the quality of their environments and maximize reproductive success by phasing breeding activities with the most favorable time of year. Whereas the specific mechanisms driving seasonal changes in reproductive function vary across species, converging lines of evidence suggest gonadotropin-inhibitory hormone (GnIH) serves as a key component of the neuroendocrine circuitry driving seasonal changes in reproduction and sexual motivation in some species. In addition to anticipating environmental change through transduction of photoperiodic information and modifying reproductive state accordingly, GnIH is also positioned to regulate acute changes in reproductive status should unpredictable conditions manifest throughout the year. The present overview summarizes the role of GnIH in avian and mammalian seasonal breeding while considering the similarities and disparities that have emerged from broad investigations across reproductively photoperiodic species.